New Earth Politics : Essays from the Anthropocene - Nicholson, Simon (Simon James); Jinnah, Sikina, 1977- (Book collections on Project MUSE., 2016)
Prominent scholars and practitioners in the field of global environmental politics consider the ecological and political realities of life on the new earth, and probe the field's deepest and most enduring questions at a time of increasing environmental stress. Arranged in complementary pairs, included are - reflections on environmental pedagogy, analysis of new geopolitical realities, reflections on the power of social movements and international institutions, and calls for more compelling narratives to promote environmental action.